Opening van het NV-huis. Op podium van links naar rechts: Fimmen, Stenhuis en Moltmaker. Uit: L6/81 (1926)
Opening van het NV-huis. Op podium van links naar rechts: Fimmen, Stenhuis en Moltmaker. Uit: L6/81.